Serial measurements of cardiac troponin I in heart failure secondary to canine mitral valve disease - Chan, I-Ping; Wu, San-Yu; Chang, Chao-Chin; Chen, Wen-Ying (Veterinary record, 2019)
Serial measurements of cardiac troponin I (cTnI) levels are considered to be better predictors of cardiac death than single-time-point analyses in human medicine. We hypothesised that cTnI levels could reflect the severity of myxomatous mitral valve disease (MMVD), and that serial changes in the cTnI level had a prognostic value in dogs with congestive heart failure (CHF) secondary to MMVD. Seventy-six dogs were initially enrolled and classified by the American College of Veterinary Internal Medicine (ACVIM) staging system. The single-timepoint cTnI concentration in these dogs significantly increased with the ACVIM stage. Twenty-seven dogs with CHF subsequently underwent serial measurement of cTnI levels, and the results showed that those who demonstrated a decrease in cTnI levels from the first to the third visit exhibited a higher risk of cardiac death than did those without such changes (P=0.012). We suspect that the downward trend in cTnI levels may be affected by medical treatment for CHF. In conclusion, although cTnI levels could reflect the severity of MMVD to a certain extent, the serial changes may be affected by medical treatment. Therefore, caution should be exercised when cTnI is used for assessment of the prognosis of CHF secondary to MMVD in dogs.